Influence of sea level rise on the dynamics of salt inflows in the Baltic Sea. Issue 10 (14th October 2015) - Hordoir, Robinson; Axell, Lars; Löptien, Ulrike; Dietze, Heiner; Kuznetsov, Ivan
Abstract: The Baltic Sea is a marginal sea, located in a highly industrialized region in Central Northern Europe. Saltwater inflows from the North Sea and associated ventilation of the deep exert crucial control on the entire Baltic Sea ecosystem. This study explores the impact of anticipated sea level changes on the dynamics of those inflows. We use a numerical oceanic general circulation model covering both the Baltic and the North Sea. The model successfully retraces the essential ventilation dynamics throughout the period 1961–2007. A suite of idealized experiments suggests that rising sea level is associated with intensified ventilation as saltwater inflows become stronger, longer, and more frequent. Expressed quantitatively as a salinity increase in the deep central Baltic Sea, we find that a sea level rise of 1 m triggers a saltening of more than 1 PSU. This substantial increase in ventilation is the consequence of the increasing cross section in the Danish Straits amplified by a reduction of vertical mixing. Key Points: Sea level rise increases the salinity of the Baltic Sea This increase is related to more frequent and stronger salt inflows One notices a decreased mixing and a bigger cross section in the Danish Straits